VGM business portraits Boeing - Gould, William 1947- (Lincolnwood, Ill. VGM Career Horizons, 1995)
Introduces basic business concepts, using Boeing Corporation as a case study.
Keywords: Boeing Company -- Juvenile literature; Boeing Company; Aircraft industry -- United States -- Juvenile literature; Aircraft industry